Compressive of the first disc Δı (t) of the commuting graph C (G, X) for elements of order three in symmetric groups - Nawawi, Athirah; Rowley, Peter (AIP Publishing, 2016)
The commuting graph C (G, X), where G is a finite group and X is a subset of G, is the graph whose vertex set is X and two distinct elements of X being joined by an edge whenever they commute in the group G. Here the CG (t) orbit representatives and the number of elements in the first disc Δı (t) of C (G, X), is studied when G is a symmetric group of degree n, Sym (n) and X is a conjugacy class of elements of order three.